Air pollution and cardiovascular admissions association in Spain: results within the EMECAS project. Issue 4 (13th March 2006) - Ballester, F; Rodríguez, P; Iñíguez, C; Saez, M; Daponte, A; Galán, I; Taracido, M; Arribas, F; Bellido, J; Cirarda, F B; Cañada, A; Guillén, J J; et al.
Abstract : Objective: To evaluate the short term effect of air pollution on cardiovascular admissions in 14 Spanish cities Methods: The period under study was from 1995 to 1999. Daily emergency admissions for all cardiovascular diseases (CVD) and heart diseases (HD) were obtained from hospital records, and the corresponding daily levels of particulates, SO2, NO2, CO, and ozone were recorded. The magnitude of association was estimated using Poisson generalised additive models controlling for confounding and overdispersion. For each cause, lagged effects, up to three days, of each pollutant were examined and combined estimates were obtained. For ozone the analyses were restricted to the warm period. One and two pollutant models were performed. Results: Associations were more consistent in lag 0 (concurrent day) and 1 (lag 0–1), except in the case of ozone where there was a more delayed relation (lag 2–3). For combined estimates an increase of 10 μg/m 3 in the PM10 levels in lag 0–1 was associated with an increase of 0.9% (95% CI: 0.4 to 1.5%) in the number of hospital admissions for CVD, and 1.6% (0.8 to 2.3%) for HD. For ozone the corresponding estimates for lag 2–3 were 0.7% (0.3 to 1.0) for CVD, and 0.7% (0.1 to 1.2) for HD. An increase of 1 mg/m 3 in CO levels was associated with an increase of 2.1% (0.7 to 3.5%) in CVD admissions, and 4.2% (1.3 to 7.1%) in HD admissions. SO2 and NO2 estimates were more sensitive in two pollutant models Conclusions: A short term association between increases in daily levels of air pollutants and the number of daily admissions for cardiovascular diseases, with specificity for heart diseases, has been described in Spanish cities.